Analisis Yuridis Perlindungan Hukum terhadap Korban Kejahatan Berbasis Teknologi Kecerdasan Buatan/Artificial Intelligence (AI) - Obe, Elfrida Tipe; Sinurat, Aksi; Fanggi, Rosalind Angel (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Artificial Intelligence (AI) based crimes are a modern form of criminal offense that exploits AI technology to harm individuals or groups. This study aims to analyze existing legal frameworks and the challenges in implementing legal protection for victims of AIbased crimes. The research focuses on two main questions: (1) How is the legal framework structured for victims of AI related crimes? and (2) What are the implementation challenges and possible solutions for ensuring legal protection? The research uses a normative legal method through literature review and secondary data analysis. The findings reveal that while several laws can be applied to prosecute offenders, the protection of victims remains insufficient and lacks explicit regulation. Key challenges include regulatory gaps, difficulties in tracing and proving AI-related offenses, limited human and technological resources in law enforcement, and issues of privacy and data security. To address these challenges, it is necessary to formulate AI-specific regulations, establish accessible and responsive reporting mechanisms, raise public awareness, and create specialized law enforcement bodies. The study recommends legal reform that prioritizes the protection of victims’ rights in the face of emerging digital threats.